2015
DOI: 10.1007/s11356-015-5161-8
|View full text |Cite
|
Sign up to set email alerts
|

The response and detoxification strategies of three freshwater phytoplankton species, Aphanizomenon flos-aquae, Pediastrum simplex, and Synedra acus, to cadmium

Abstract: The response and detoxification mechanisms of three freshwater phytoplankton species (the cyanobacterium Aphanizomenon flos-aquae, the green alga Pediastrum simplex, and the diatom Synedra acus) to cadmium (Cd) were investigated. The cell growth of each species was measured over 10 days, and chlorophyll a fluorescence, Cd bioaccumulation (including surface-adsorbed and intracellular Cd), and phytochelatin (PC) synthesis were determined after 96-h exposures. The growth of the three phytoplankton species was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Ni and As contributed 26 and 21% of the potential ecological risk, respectively. Ran et al (2015) suggested that the algal biomass may be reduced as the Cd pollution in an aquatic ecosystem increases over the maximum limit of 1.0 mg/L. Several studies have reported that metals adversely influence the diversity of the microbial community in the bottom sediment (Ran et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Ni and As contributed 26 and 21% of the potential ecological risk, respectively. Ran et al (2015) suggested that the algal biomass may be reduced as the Cd pollution in an aquatic ecosystem increases over the maximum limit of 1.0 mg/L. Several studies have reported that metals adversely influence the diversity of the microbial community in the bottom sediment (Ran et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Ran et al (2015) suggested that the algal biomass may be reduced as the Cd pollution in an aquatic ecosystem increases over the maximum limit of 1.0 mg/L. Several studies have reported that metals adversely influence the diversity of the microbial community in the bottom sediment (Ran et al 2015). At the same time, variations in the microbial community may exist due to indirect ecological risks (Zhu et al 2017).…”
Section: Resultsmentioning
confidence: 99%